Hygrothermoelastic analysis of anisotropic cylindrical shells - Alsubari, Saleh; Mohamed Ali, Jaafar Syed; Aminanda, Yulfian (Elsevier, 2015)
In this work, the combined effect of moisture and temperature on the bending behavior of simply supported anisotropic cylindrical shells has been investigated. Initially three dimensional equilibrium equations of thermoelasticity, simplified to the case of generalized plane strain deformations in the axial direction are solved analytically for an anisotropic cylindrical shell strip under thermal loading. Based on the realistic variation of displacements from the elasticity approach, a new 13 term higher order shear deformation theory HSDT13 was proposed for the analysis of an anisotropic cylindrical shell strip under hygrothermal and mechanical loading. The zigzag form of the displacement is incorporated via the Murakami zigzag function. Results are presented for mechanical and thermal loading for various layups and they are validated against the derived elasticity solution. The significance of retaining various higher-order terms in the present model HSDT13, in evaluating the stresses and deflection for composite laminates is brought out clearly through parametric study. Useful results for combined hygrothermal loading are presented in tabular and graphical form. It is expected that the numerical results presented herein will serve as bench mark in future.